Circumbinary, not transitional: on the spiral arms, cavity, shadows, fast radial flows, streamers, and horseshoe in the HD 142527 disc. Issue 1 (15th March 2018) - Price, Daniel J; Cuello, Nicolás; Pinte, Christophe; Mentiplay, Daniel; Casassus, Simon; Christiaens, Valentin; Kennedy, Grant M; Cuadra, Jorge; Sebastian Perez, M; Marino, Sebastian; Armitage, Philip J; Zurlo, Alice; et al.
Abstract: We present 3D hydrodynamical models of the HD 142527 protoplanetary disc, a bright and well-studied disc that shows spirals and shadows in scattered light around a 100 au gas cavity, a large horseshoe dust structure in mm continuum emission, together with mysterious fast radial flows and streamers seen in gas kinematics. By considering several possible orbits consistent with the observed arc, we show that all of the main observational features can be explained by one mechanism – the interaction between the disc and the observed binary companion. We find that the spirals, shadows, and horseshoe are only produced in the correct position angles by a companion on an inclined and eccentric orbit approaching periastron – the 'red' family from Lacour et al. Dust–gas simulations show radial and azimuthal concentration of dust around the cavity, consistent with the observed horseshoe. The success of this model in the HD 142527 disc suggests other mm-bright transition discs showing cavities, spirals, and dust asymmetries may also be explained by the interaction with central companions.